Digitalisasi Pembukuan UMKM Menggunakan Aplikasi Akuntansi Gratis di Smartphone - Hamdani Hamdani; Indra Gunawan Siregar; Ardhida Sata; Bayu Wahyu Buana; Dimas Vernando Vargas; Dicky Derryansyah Siregar; Muhammad Faris Hawasi (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) continue to face challenges in financial management due to manual bookkeeping practices, which increase the risk of financial leakage and hinder business performance monitoring. This community service program aimed to improve MSME owners' ability to utilize free smartphone-based accounting applications to create simple, organized, and accurate financial records, thereby reducing financial leakage and supporting more effective and efficient business management through digital transaction recording. The program was conducted through an online seminar and training session via Zoom using a participatory approach. Activities included presentations on the importance of digital bookkeeping for MSMEs, practical demonstrations of installing and using free accounting applications, business account setup, recording sales and purchase transactions, generating financial reports, interactive discussions, and participant evaluations. The results showed a significant improvement in participants' understanding of the benefits of digital bookkeeping compared with manual recording, particularly regarding speed, accuracy, and accessibility of financial data. Participants also acquired practical skills in recording daily transactions, monitoring cash flow, and generating automated financial reports using smartphone applications. Consequently, they were better able to identify potential financial leakages and implement more organized and modern financial management practices. In conclusion, the online seminar successfully enhanced participants' digital literacy and understanding of free smartphone-based accounting applications as an affordable and practical solution for MSME bookkeeping digitalization, while contributing to improved financial governance and business sustainability.